Deteksi dan Identifikasi Pembentuk Perilaku Herding Pada Indeks Harga Saham Gabungan Periode 2008 dan 2016 - Valdo Valiant Ravanola (Jurnal Ilmiah Mahasiswa FEB, 2016)
The aims of this research is to detect and identify the cause of herd behavior in Jakarta Composite Index during 2008 and 2016 periods. Those two periods is choosen to represent market condition during normal and market stress condition. Using Chang, Cheng, and Khorana (2000)’s method that extends the work of Christie and Huang (1995) to measure dispersion return by Cross Sectional Absolute Deviation and adding the non-linear approach  with regression analysis as tools to detect herd behavior.By collecting data from daily individual’s and market’s stock return from the companies in Jakarta Composite Index that is choosen using purposive sampling method in each year of observation to determine dispersion rate as Chang, Cheng, and Khorana (2000)’s methode suggest, this research shows that there is non-linearity relation between squared market’s return and dispersion rate which is the indication of herd behavior during 2008 and 2016 periods. From the initial result that shows there is indication of herd behavior, the other aim of this reasearch is also to identify the cause of herd behavior by using supportive data from interviews to brokers and investors that is doing their transactions in Indonesian stock market. The interviews shows similar results that according to the informans, they often find irrational behavior from the investors in their decision. The informans also said that the investor sometimes act only based on other’s investor private information, implying that informational cascades is one of the main cause of herd behavior that is occuring in Jakarta Composite Index.                                                                               Keywords : Herd Behavior,, Behavioral Finance, Cross Sectional Absolute Deviation